Pendekatan Manajemen Strategi pada Pertumbuhan dan Daya Saing di Sektor Perbankan Syariah - Istiyadah, Narulita Al Kholifina (Maliki Interdisciplinary Journal, 2025)
This study explores the role of strategic management in supporting the growth and competitiveness of Islamic banking amidst increasing competition. Islamic banking, based on Sharia economic principles, faces significant challenges such as ever-changing regulations, competition with conventional banks, and the need for innovation in financial technology (fintech). This article highlights how the right strategies can help Islamic banks leverage market opportunities, enhance operational efficiency, and develop products that align with Sharia principles. External factors such as regulations, technology, and consumer preferences, as well as internal factors like the quality of human resources and organizational structure, play key roles in achieving competitive advantage. With a focus on technological innovation, product diversification, and performance evaluation, Islamic banks can effectively compete in the increasingly complex and dynamic financial industry.